Characterization and measurement of dehydroepiandrosterone sulfate in rat brain. - Corpéchot, C (1981)
Dehydroepiandrosterone (3 beta-hydroxy-5-androsten-17-one, I) sulfate (Ia) has been characterized in the anterior and the posterior parts of the brain of adult male rats. Its level (1.58 +/- 0.14 and 4.89 +/- 1.06 ng/g, mean +/- SD, in anterior and posterior brain, respectively) largely exceeded that of I in brain (0.42 +/- 0.10 and 0.12 +/- 0.03 ng/g in anterior and posterior brain, respectively) and of Ia in plasma (0.26 +/- 0.13 ng/ml). Brain Ia level did not seem to depend on adrenal secretion; it was unchanged after administration of corticotropin or dexamethasone for 3 days, and no meaningful change occurred in brain 15 days after adrenalectomy plus orchiectomy, compared with sham-operated controls. In contrast, stress conditions prevailing 2 days after adrenalectomy plus orchiectomy or after the corresponding sham operation resulted in a significantly increased concentration of Ia in the brain. Changes of Ia level in brain occurred irrespective of changes in corresponding plasma samples. It is proposed that Ia formation or accumulation (or both) in the rat brain depends on in situ mechanisms unrelated to the peripheral endocrine gland system.